Cassava breeding: A multidisciplinary review: Proceedings of a workshop, held in the Philippines, 4-7, March 1985 - Hershey, Clair H. (International Center for Tropical Agriculture, 1987)
Cassava breeders and scientists in related fields from the 3 major cassava-producing continents (America, Africa, and Asia) were brought together for the lst time to discuss the latest advances in cassava breeding research and exchange ideas on future priorities. Most breeding programs now orient their research towards breeding for efficiency under suboptimal conditions. The concern for yield stability is equal to or greater than that of breeding for yield potential. A low-input philosophy of integrated pest and disease management, based on host plant resistance, has come to the forefront. Novel approaches are also being applied to plant germplasm management and breeding such as in vitro cultures, anther culture for haploid production, cryopreservation, protoplast fusion, in vitro selection, and recombinant DNA and gene-transfer technology. (CIAT)